(untitled) (Agro Productividad, 2025)
Objective: To evaluate an alternative culture medium based on moringa (Moringa oleifera) leaves and enriched with growth regulators that could improve seed germination efficiency in a controlled environment. This alternative method was compared with conventional methods; in addition, the benefits of using nutrient-dense natural components for the species G. aurantiaca were analyzed. Design/Methodology/Approach: Dehydrated moringa leaves were used to prepare the in vitro culture media. Their effect on the germination of G. aurantiaca was evaluated using a completely randomized experimental design. Meanwhile, an analysis of variance and Tukey’s test were used to compare means. The variables included different moringa leaf (7, 10, and 15 g/L-1) and growth regulator concentrations. The dependent variable was germination percentage. Study Limitations/Implications: The availability of G. aurantiaca seeds was a limiting factor. Results: After 47 days, the MS medium with GA3 (0.1 mg/L-1) achieved the highest germination rate (91%). Ninety-seven days after sowing, the moringa leaf-based medium, with a 10 g/L-1 concentration and enriched with GA3 (0.1 mg/L-1), achieved an 89% germination rate. Findings/Conclusions: The culture medium enriched with moringa leaves is an efficient alternative for the in vitro germination of G. aurantiaca. These results established for the first time that the moringa-based culture medium is an effective alternative for the germination and conservation of this species.